2002
DOI: 10.1103/physrevb.66.214521
|View full text |Cite
|
Sign up to set email alerts
|

Possible reordering of vortex matter near the end point of the second peak line in theYBa2Cu3O

Abstract: We report on the second peak line H sp and the possible phases of vortex matter near T c for a detwinned underdoped YBa 2 Cu 3 O 7Ϫ␦ single crystal. Our local ac and dc permeability measurements revealed that the second peak line H sp does not terminate either at the critical temperature or on the irreversibility line H irr . Pronounced hysteretic behavior is observed in the regime below the second peak line H sp . Below ͑above͒ a characteristic field the end point of the second peak differs from ͑coincides wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 67 publications
3
22
0
Order By: Relevance
“…First of all, we observe that the H irr (T ) data exhibit a slight upward curvature, which is reminiscent of the behavior observed in type-II high and low-T c [4,5,6,17,19], or even type-I [41] superconductors. As we clearly see, the irreversibility points T irr (H) as determined from isofield magnetic measurements as a function of temperature (solid triangles), do not coincide with the respective points H irr (T ) as determined from isothermal magnetic loop measurements (open triangles).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…First of all, we observe that the H irr (T ) data exhibit a slight upward curvature, which is reminiscent of the behavior observed in type-II high and low-T c [4,5,6,17,19], or even type-I [41] superconductors. As we clearly see, the irreversibility points T irr (H) as determined from isofield magnetic measurements as a function of temperature (solid triangles), do not coincide with the respective points H irr (T ) as determined from isothermal magnetic loop measurements (open triangles).…”
Section: Resultsmentioning
confidence: 72%
“…This behavior may be seen in fig. 3 for three representative temperatures T = 4.3, 5 and 6 K. The overall behavior resembles the SMP observed usually in high-T c superconductors [16,17,18,19,20]. For this reason we "loosely" refer to these characteristic fields as H′′ smp ′′ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result the magnetic curves are more regular. The overall behavior resembles the SMP observed usually in high-T c superconductors [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. For this reason we "loosely" refer to these characteristic fields as H′′ smp ′′ .…”
Section: Tmis and The "Smp" In Magnetic Measurementsmentioning
confidence: 99%
“…Recent magnetic studies in Nb films [1,2,3] reported the existence of a structure that reminisces of the second magnetization peak (SMP) which is usually observed in high-T c superconductors [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. These studies concluded that for the case of Nb films the "SMP" is probably motivated by thermomagnetic instabilities (TMIs) that occur in the low-temperature regime, far below the uppercritical field [1,2,3].…”
Section: Introductionmentioning
confidence: 99%